(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the influence of a complex of preparations on seeds and plants, focusing on phenological characteristics, plant growth and development, and melon yield. In terms of taste qualities, melons are on par with the most exquisite fruits. Melon fruits are consumed both fresh and processed. As early as the 6th century, the Spanish botanist Herrera wrote: "If it is good, then it is the best of fruits, and no other can surpass it." Due to the special value of fresh melons, they are processed in smaller quantities than watermelons.